含长链烷基季铵盐的纳米抗菌无机填料的合成及其在牙科复合树脂中的应用研究 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2014)
OBJECTIVE: This study aimed to synthesize a novel nano-antibacterial inorganic filler that contains a quaternary ammonium salt with long chain alkyl and to report the antibacterial property of dental resin composites. METHODS: A novel nano-antibacterial inorganic filler that contains a quaternary ammonium salt with long chain alkyl was synthesized based on previous research. The antibacterial property of the filler was measured. The surface of the novel nano-antibacterial inorganic filler was modified by a coupling agent to achieve a good interfacial bonding between the filler and the resin matrix. Infrared spectrum analysis was carried out. The modified novel nano-antibacterial inorganic fillers were then incorporated into the dental resin matrix. The dispersion of the fillers was observed and compared with those incorporated into Tetric N-Ceram, a commercial resin composite, under a scanning electron microscope. Streptococcus mutans was used in testing the antibacterial property of the dental resin composites. RESULTS: A quaternary ammonium salt with a long chain alkyl was successfully grafted onto the surface of nano-silica particles. The novel nano-antibacterial inorganic filler that contains quaternary ammonium salt with a long chain alkyl showed stronger antibacterial efficacy than the antibacterial inorganic filler that contains quaternary ammonium salt with a short chain alkyl. The modified novel antibacterial inorganic fillers displayed a homogeneous dispersion in the resin composite bulk and combined closely with the resin matrix, similar to the Tetric N-Ceram. The resin com-posites that contain novel antibacterial inorganic fillers showed stronger antibacterial effect on Streptococcus mutans compared with the control group. CONCLUSION: The novel nano-antibacterial inorganic filler that contains a quaternary ammonium salt with long chain alkyl showed a strong antibacterial property. It also exhibited good compatibility with the dental resin matrix after undergoing coupling treatment.